2007
DOI: 10.1007/s00193-007-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dimples on glancing shock wave turbulent boundary layer interactions

Abstract: An experimental study has been conducted to examine the control effectiveness of dimples on the glancing shock wave turbulent boundary layer interaction produced by a series of hemi -cylindrically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…1, where γ is the specific heat ratio, ρ is the density, M is the Mach number and subscripts 0 and jet refer to freestream and jet conditions. Schlieren photography [40][41][42][43][44] was employed to visualize the flow field around the cavity in a standard Z-type optical arrangement. A pair of 203.3 mm diameter parabolic mirrors with 1016 mm focal length and a 150W Hamamatsu Xenon continuous light source were used.…”
Section: Methodsmentioning
confidence: 99%
“…1, where γ is the specific heat ratio, ρ is the density, M is the Mach number and subscripts 0 and jet refer to freestream and jet conditions. Schlieren photography [40][41][42][43][44] was employed to visualize the flow field around the cavity in a standard Z-type optical arrangement. A pair of 203.3 mm diameter parabolic mirrors with 1016 mm focal length and a 150W Hamamatsu Xenon continuous light source were used.…”
Section: Methodsmentioning
confidence: 99%
“…The position of the hot wire was measured to an accuracy of 0.25 mm with a repeatability of 0.06 mm. The pressure measurements via the aid of pressure transducers were repeated twice and had a repeatability of 99% [32].…”
Section: Methodsmentioning
confidence: 99%
“…The description of this technique along with its merits over conventional pressure measurement techniques are well documented in the literature. [32][33][34][35][36][37] The in-house developed PSP technology used in the present study has been successfully applied in a variety of flow conditions and has been found in all cases to provide accurate pressure measurements when compared to conventional pressure transducers. [38][39][40][41][42][43][44] The PSP setup consists of a LaVision Image Intense 12-bit CCD camera with a 590nm long-pass filter mounted on the lens, and UV LEDs with peak wavelength of 390nm were used for image acquisition.…”
Section: B Measurement Techniquesmentioning
confidence: 99%